2005
DOI: 10.1111/j.1466-7657.2004.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian baccalaureate nursing students’ perception of their learning styles

Abstract: Based on the study findings, it is suggested that nurse educators should provide positive reinforcement of students' active involvement in the learning process, which will stimulate continued self-direction. Moreover, courses on study skills, writing skills, and literature searching skills should be introduced early in nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
4
11
1
Order By: Relevance
“…However, the present study's results were identical to those reported in previous studies conducted in China (Yuan et al 2012, p. 427) and Australia (Fisher et al 2001). However, the current study's findings did not align with those in the Jordanian study (Abu-Moghli et al 2005), which found that nursing students were perceived as independent learners, and the majority of the students indicated a desire to learn. Regarding the levels of SDLR, most of the participants had low levels of SDLR (score ≤ 150).…”
Section: Discussioncontrasting
confidence: 51%
“…However, the present study's results were identical to those reported in previous studies conducted in China (Yuan et al 2012, p. 427) and Australia (Fisher et al 2001). However, the current study's findings did not align with those in the Jordanian study (Abu-Moghli et al 2005), which found that nursing students were perceived as independent learners, and the majority of the students indicated a desire to learn. Regarding the levels of SDLR, most of the participants had low levels of SDLR (score ≤ 150).…”
Section: Discussioncontrasting
confidence: 51%
“…In a longitudinal study, Rakoczy and Money (1995) examined learning styles and found the “assimilator”, or one who demonstrates an ability to understand large quantities of data by putting the data into a concise, logical form, was the most common style used. Jordanian baccalaureate nursing students have been found to be “independent learners” or ones who desire to learn new things and are independent in identifying personal goals (Abu‐Moghli et al. , 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The questionnaire was then pilot tested on a sample of nursing students at four of six Jordanian universities offering a baccalaureate degree in nursing. Abu-Moghli et al (2005) reported that the instrument was reliable (α = 0.89) in measuring learner independence of baccalaureate nursing students. There are no identified U.S. published studies using the ALI.…”
Section: Instrumentationmentioning
confidence: 99%
“…Explore the total scores of baccalaureate nursing students on the Academic Motivation Scale (AMS) (Vallerand, Pelletier, Blais, Briére, Senécal, & Vallières, 1992), the Autonomous Learner Index (ALI) (Abu-Moghli, Khalaf, Halabi, & Wardam, 2005), the Curiosity and Exploration Inventory II (CEI II) (Kashdan et al, 2009), and the Self-Directed Learning Readiness Scale for Nursing Education (SDLRSNE) (Fisher et al, 2001); 2. Explore the relationships among motivation to learn, learner independence, intellectual curiosity, and SDLR of baccalaureate nursing students.…”
Section: Purposes Of Studymentioning
confidence: 99%
See 1 more Smart Citation